HUBUNGAN ASUPAN NATRIUM, AKTIVITAS FISIK, DANKUALITAS TIDUR DENGAN HIPERTENSI PADAPENGEMUDI BUS DI TERMINAL KALIDERES - Devina Alifia Salsabila (2023)
Hypertension is a common health problem affecting people all over the world. Bus drivers are prone to hypertension due to long periods of sitting and high stress. Several factors have been identified as possible triggers for hypertension, including sodium intake, physical activity, and sleep quality. This study aimed to investigate the relationship between sodium intake, physical activity, sleep quality, and hypertension in bus drivers at Kalideres Terminal. A cross sectional study design was used to collect data from 70 bus drivers at Kalideres Terminal using the Accidental Sampling technique. The data used are primary data obtained from filling out questionnaires. Relationship analysis performed using the chi-square test. The results of the analysis showed that there was a relationship between the variables of sodium intake (p = 0.022), physical activity (p = 0.016) and sleep quality (p = 0.003) with blood pressure p value < 0.05. This shows that there is a relationship between sodium intake, physical activity and sleep quality and blood pressure in bus drivers at Kalideres Terminal.